PERANCANGAN PROTOTYPE JARINGAN SENSOR MEMANFAATKAN JARINGAN WIFI MENGGUNAKAN ARDUINO UNO - Suhada Suhada; Hasdari Helmi; A M H Pardede (Jurnal Informatika Kaputama (JIK), 2019)
There is a waste in various rooms/buildings, for example, the room lights keep burning even though the room is not being used for lectures even on holidays, there must be a solution. Among the solutions is the availability of a sensing/monitoring system so that this situation can be monitored from a certain point/place in the building environment, for example, the Tunas Bangsa Academy Building. Thus this wasteful state can be reduced or even eliminated. One of the problems in building the provision of remote sensing systems is the high cost of the transmission media to be used. This problem can be overcome by utilizing existing networks, namely WiFi networks. Therefore, in this paper, a prototype sensor network is used to utilize existing WiFi networks to overcome the inefficiency (waste) of electrical energy in various rooms/buildings. From the results of the design of the sensor network can work well in WiFi network environments that can be used to monitor energy inefficiencies in a building's environment.